Pelatihan Disiplin Positif bagi Guru dalam Mendukung Lingkungan Sekolah Inklusif bagi Siswa Pengungsi - Sinta Nurul Oktaviana Kasim; Farida Aryani; Siti Raihan; Yusri (BALE LITERASI, 2026)
Makassar City, characterized by diverse student backgrounds including refugee students, requires teachers to create inclusive and supportive learning environments. However, classroom behavior management practices are still often dominated by punitive approaches that are less constructive. This community service program aims to enhance teachers’ understanding of positive discipline in managing student behavior. The method used was a capacity-building training with a participatory approach, including interactive lectures, group discussions, case studies, and role play, involving 53 teachers from various educational levels in Makassar. Data were collected through a Likert-scale survey administered after the training to assess participants’ understanding. The results indicate that the majority of participants demonstrated a positive understanding of positive discipline concepts, reflected in the rejection of physical punishment (more than 70%), increased awareness of the importance of positive reinforcement (81.1%), and recognition that handling behavioral issues and bullying is a shared responsibility. These findings suggest that the training effectively fostered a more constructive, empathetic, and participatory perspective among teachers in managing student behavior. The program implies the need for continuous support through follow-up mentoring to ensure consistent implementation of positive discipline practices in schools.